Role of succession planning and entrepreneurial thinking towards the performance of family- owned businesses - Suleman, Areeba; Muhammad, Armanurah Binti; Zakaria, Nazlina (International Journal of Psychosocial Rehabilitation, 2020)
Family-owned businesses were considered as the oldest form of businesses and major chunk in every sector. Family-owned businesses particularly SMEs receive a good deal of attraction and prestige from academicians and policymakers, even backing economies for long-time. The underpinning objective of current study is to test the role of succession planning (structural, cognitive, and relational ties) and entrepreneurial thinking (identifying opportunity, risk taking, tolerance of ambiguity and creative & innovative) towards the performance. The findings indicate that the succession planning, structural, cognitive, and relational have a positive and significant relationship with the firm performance. Moreover, entrepreneurial thinking identifying opportunity, risk- taking, tolerance of ambiguity, and creative & innovation have a positive and significant relationship with firm performance. The current study considered the subjective firm performance based on financial and non-financial dimensions. The future studies need to consider the role of family structure and culture towards the succession planning process.